Optimisation of a railway sanding system for optimal grain entrainment into the wheel–rail contact. (January 2018) - Lewis, SR; Riley, S; Fletcher, DI; Lewis, R
To combat adhesion loss, sand is fired into the wheel–rail contact via a hose using compressed air typically from a storage hopper mounted to the under frame of the train. Many passenger trains in the UK are fitted with stepped braking controllers which range from 1 to 3 with a fourth step being 'emergency braking'. 1 Sand is fired automatically if wheel slip is detected from brake step level 2 upwards. 2 Sand is automatically fired when the emergency brakes are applied irrespective of whether low adhesion/wheel slip has been detected. 2 For adhesion loss in traction, sand can be applied at the driver's discretion. Current railway standards 2 govern the maximum permissible sand flow rate to protect against wheel/rail isolation of track circuits, but do not address the hose position. This results in a range of hose set-ups across different train types, some of which may not be effective at delivering sand. The work here was carried out using a full-scale laboratory rail–wheel test machine to find the position for the hose and sand flow rates that give optimum sand entrainment to the contact. It was found that ideally the hose should be aimed at the rail or nip and be as close to that contact as safely possible. The use of a 20 mm bore nozzle on the end of a 25 mm bore hose increased sand passing through the contact by up to 70% relative to widely used 25 mm bore hoses without a nozzle. Reduction in sand flow rate below the 2 kg/min threshold significantly reduced the amount of sand entering the contact. It was also shown that relatively small movements in the hose/nozzle from its ideal position and cross winds significantly reduced sand entrainment.